A combination of tri-modal cancer imaging and in vivo drug delivery by metal–organic framework based composite nanoparticles. (11th September 2015) - Bian, Ruixin; Wang, Tingting; Zhang, Lingyu; Li, Lu; Wang, Chungang
<x xml:space="preserve">Abstract</x> A facile method was developed for the synthesis of multifunctional Fe3O4@PAA/AuNCs/ZIF-8 NPs. Furthermore, the obtained NPs with ultrahigh drug storage capacity and dual pH-responsive drug release properties were applicable in simultaneous tri-modal.